Combining electronic and steric effects for highly stable unsymmetric pentacenes. - Zhang, Jingjing.; Pawle, Robert H.; Haas, Terry E.; Thomas, Samuel W., III. (Tufts University. Tisch Library., 2018)
This paper describes the reactivity of unsymmetrically substituted pentacenes to photochemical oxidation. Acenes in general, and pentacenes in particular, are a key family of compounds for a variety of organic electronics applications. The instability of many pentacene derivatives, particularly to oxidation, is an important restriction in their applicability. Several substitution strategies for decreasing the reactivity of pentacene exist, but these almost always involve symmetrically substituted derivatives, restricting the chemical space of structures from which to choose. In this paper, we demonstrate that combining electronic and steric effects yields highly stable unsymmetrically substituted pentacenes. High fives! Highly stable pentacene derivatives are described, which combine an electronically deactivating alkyne substituent with a sterically-encumbering dialkylaryl substituent on the reactive 6- and 13-positions (see scheme) Resistance to photooxidation of these unsymmetrically substituted pentacenes is comparable to diethynylpentacenes, opening new chemical space for the discovery of stable organic semiconductors.